"Inamura no hi" ("the rice bale fire"), its evolving story and global relevance: the politics of tsunami preparedness in Japan. Issue 2 (1st October 2020) - Thompson, Christopher Scott
Abstract : Purpose: This paper aims to reintroduce to proponents of natural disaster readiness worldwide the history and content of the most renowned tsunami mitigation tale in Japan, " Inamura no Hi " ("The Rice Bale Fire") for the purpose of reconnecting with its many virtues that have made it a cross-cultural pedagogical catalyst for tsunami preparedness education. At a time in the planet's history when global warming mitigation and pandemic advertence in a milieu in which equity, diversity and human rights are highly valued, the insights it contains pertaining to tsunami preparedness, plot design and the politics of its popularity make it particularly instructive. Design/methodology/approach: The study used methods, approaches and techniques prevalent in cultural anthropology, i.e. primary texts, historical analysis, linguistic natural hazard preparedness education theory and ethnographic insights to assess how and why " Inamura no Hi " ("The Rice Bale Fire") has come to be used so broadly on an international scale as a tsunami preparedness teaching tool and the politics involved in this process. Findings: The study revealed that the cross-cultural relevance of " Inamura no Hi " ("The Rice Bale Fire") is related to its unique authorship and development which has cultivated in it three qualities highly compatible with effective disaster mitigation at the international level. These are the simplicity of its message, the practical advice it dispenses and the universally agreeable morality it supports. However, the way in which the Japanese Government has promoted this story does not effectively encourage equity, diversity, or a respect for human rights as a major facilitator of preparedness among the many nations like itself in the region and in the world that are vulnerable to natural hazards. Research limitations/implications: The main limitations of the study are that it is based on a historic investigation of the origins of " Inamura no Hi " ("The Rice Bale Fire") using materials in English and Japanese, a genealogical interpretation of the story using approaches prevalent in translation studies and a qualitative analysis of historical uses of the story, all of which are difficult to quantify. Since the study seeks to find social and cultural patterns in the relevant material presented, the analysis reflects a subjectivity common in all social scientific studies of this kind. Practical implications: Educating its readers about tsunami preparedness is one of the most important functions of this paper. The study confirms that " Inamura no Hi " ("The Rice Bale Fire") provides Japanese and non-Japanese alike with the opportunity to envision and construct a customized culturally specific sense of tsunami readiness by harnessing this dynamic. For Japanese, the story provides a chance to contemplate an astute view of Japanese-style tsunami management from the viewpoint of an outsider who became a well-respected citizen. For non-Japanese, the story offers an opportunity to be reflexive about tsunami readiness based on a cross-culturally adaptable template that Hamaguchi's protagonist Gohei provides. Social implications: Pedagogically speaking, " Inamura no Hi " ("The Rice Bale Fire") makes the most sense when regarded as a starting point for preparing for any natural disaster anywhere. The story reminds us that the most educational, globally relevant tsunami preparedness narratives are those that complement and extend the latest of what the world knows about these destructive ocean waves to keep vulnerable citizens safe and alive. This study reveals that as important as the story is the politics of its delivery to provide the best first line of defense against tsunami amnesia which in Japan and many other countries has historically taken far too many lives. Originality/value: The paper argues that " Inamura no Hi " ("The Rice Bale Fire") is an example of a tsunami preparedness story that contains a variety of insights that continue to contribute to tsunami awareness education cross culturally that must not be underestimated. However, the way it is currently promoted by the Japanese Government needs to be improved, so that more representatives from more countries involved in tsunami preparedness and natural hazard readiness worldwide can benefit. These are insights not accessible by a researcher who is not bilingual in English and Japanese; thus, by using an ethnographic approach and participant observation utilizing both languages as part of long-term fieldwork, the researcher can gain these insights.